Detection of protein interactions based on GFP fragment complementation by fluorescence microscopy and spectrofluorometry. (January 2008) - Torrado, Mario; Iglesias, Raquel; Mikhailov, Alexander T.
We have developed a set of simple modifications of the green fluorescent protein (GFP) fragment reassembly assay in bacteria that permits: ( i ) fluorescent microscopy visualization of GFP reassembly only 1-2 h after induction of protein expression, thus approximating the detection of GFP reassembly to the real-time dynamics of protein complex formation in living cells; ( ii ) spectrofluorometric detection of reassembled GFP fluorescent signals directly in lysates from cell suspension thereby avoiding, in many cases, the need for tag-affinity isolation of protein complexes; and ( iii ) comparative quantification of signal intensity in numerous cell-sample lysates using a Bio-Rad IQ5 spectrofluorometric detection system (Bio-Rad Laboratories, Madrid, Spain). Collectively, the results demonstrate that the combination of microscopic and spectrofluorometric detection provides a time-saving and sensitive alternative to existing methods of fluorescence complementation analysis.